The constructed past : experimental archaeology, education, and the public - Stone, Peter G., 1957-; Planel, Philippe G., 1948- (One world archaeology, 1999)
This collection presents a group of powerful images of the past, termed in the book as construction sites. At these sites, full scale, 3-D images from the past have been created for a variety of reasons including archaeological experimentation.